ANALISIS PENGARUH KUALITAS LAYANAN DAN KEPUASAN PASIEN TERHADAP WORDS OF MOUTH (Studi pada Pasien Rawat Jalan RS. Bhakti Wira Tamtama Semarang) - Setyawati, Indah (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2009)
The service quality are believed to have an impact on satisfaction and creating the word-of mouth activity. The purpose of this research is to test the influences of service quality on customer satisfaction to increase words of mouth.To do this, data were collected by interviewing 100 patient of RS. Bhakti Wira Tamtama Semarang. Then, data was analyzed using Structural Equation Modeling (SEM)The result shows that service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on words of mouth, and customer satisfaction has a positive and significant effect on words of mouth.The results also show that service quality has the highest effect in creating the words of mouth. Therefore, the managerial implication should place the service quality improvement as a priority.